One Stop Border Posts (OSBPs) Trade Facilitation Initiative: A Study from Rwandan Customs Posts - Vincent, Nkundabaramye (New Innovations in Economics, Business and Management Vol. 9, 2022)
Despite a critical role played by the cross-border movement of goods in international trade, the former has been shown throughout the literature to be made more complex and unpredictable by various factors. In Rwanda as is the case in other various parts of the world, the introduction and implementation of One Stop Border Posts (OSBPs) was expected to reduce and ultimately remove such factors. In particular, the purpose of OSBPs adopted, implemented and operationalised at the East African Community (EAC) level is to facilitate cross-border trade and movement of goods. This chapter therefore aims to assess the implementation of OSBPs trade facilitation initiative along the Rwandan customs posts and to examine the extent to which OSBPs initiative affects the movement of goods across the Rwandan customs posts. Descriptive statistics and Multi-Level Model were used to analyse primary data collected across different groups of trading agents. The main results stated that the implementation of OSBPs initiative has had a significant and positive impact on the movement of goods through Rwandan customs posts, implying that the implementation of OSBPs trade facilitation initiative has significantly contributed to improvements in the level of trade facilitation; and thus, streamlined and speeded up the movement of goods through Rwandan customs posts by removing the unnecessary barriers. However, this study calls for involvement and consultations of all border-crossing agencies in order to improve the implementation of OSBPs trade facilitation initiative and continue to facilitate cross-border movement of goods.